Hubungan Penggunaan Media Sosial dengan Interaksi Sosial pada Remaja di SMK Bhinneka Karya Simo Boyolali - Suyatno; Ilham Nur Hakim; Heni Purwaningsih (Jurnal Kesehatan Mahardika, 2022)
Background: Based on random interview results at SMK Bhinneka Karya Simo Boyolali. obtained all 20 students using mobile phones and social media. In addition, 15 out of 20 students participated in activities held by the community and there were 10 of them only active monthly, 5 others were active in community service and there were 5 students not active in community activities. In addition, there is also data that all students admit that they often do not immediately do their work and choose to update their status on social media. Objective: To find out the relationship between the use of social media and social interaction Method: This study uses a cross sectional design to study the dynamics of correlation. The population in this study were all 11th grade students of SMK Bhinneka Karya Simo, amounting to 34 people. The sample of this study was obtained by 34 people. The sampling technique used is total sampling and analysis using Pearson. Results: Characteristics of teenagers at SMK Bhinneka Karya Simo: as many as 2.9% of male students and 97.1% of female students, the majority of respondents aged 16 years were 82.4%, the length of use of social media students was between 10 hours which was 41.2%. Correlation test using Pearson test with p value 0.541 is still greater than 0.05 Conclusion: There is no significant relationship between the use of social media with social interaction inadolescents at Vocational School Bhinneka Karya Simo